PENERAPAN NEURAL NETWORK BERBASIS PARTICLE SWARM OPTIMIZATION UNTUK SELEKSI ATRIBUT PENENTUAN MAHASISWA DROP OUT - Septiana, Laila (Jurnal Pilar Nusa Mandiri, 2013)
The drop-out student is a student whose student status is revoked, in case of determined orders by the university. The height of drop-out students number will have an impact on the scoring of accreditation in a university. therefore, it is necessary to know what factors the students have the drop-out status are. Most of the algorithm comparison has been done in previous research. Otherwise, this research uses Neural Network with Particle Swarm Optimization based model to level up optimation value in selection attribute influencing prediction the students drop out.